Death and the Problems of Life Ending in Modern Society - Čekanauskaitė, Asta (Problemos, 2000)
This text is inspired by hot public discussions on the precedent of euthanasia in Lithuania. The debates revealed high complexity and discrepancy of views on this problem in such catholic country as Lithuania. The presence of a dose of dogmatism and hostility was evident in these debates too. The discussions encountered difficulties not only in the concrete case of life ending, it seemed that the issues of death itself were a kind of taboo. This article analyses culturological and philosophical aspects of death and the concepts of death in traditional and modern society (with reference to Z. Bauman and Ph. Aries). The investigation revealed the fact that public discussion of the problems of life ending (euthanasia. abortion, assisted suicide, etc.) is so controversial because of the still very powerful modern ideology of “life preservation at any cost”. Influenced by this ideology of life prolongation physicians use modern medical technology sometimes paying no attention even to patient’s will. One of the most difficult problems of contemporary society is the status of dying man: when he finds himself in the vortex of medical procedures he becomes unable to decide himself and to stop the running treating process. Ideology of medicine influenced by the scientific idea of progress leaves almost no place for a possibility to refuse the favours of improving medical technology. All contemporary authors agree that such situation is determined by the change of the dying place (from home to hospital) and general understanding of death as a disease. Death denies the claim of the modern science to control nature and to leave no place for any contingency, any accident. That is why it was excluded from the field of public discussions. The medicine as one of the special sciences is still influenced by the idea of progress, but the growing public and expert interest in discussing the issues related with death (euthanasia, abortion, etc.) shows obvious changes in our society.